Implementasi Perma No 1 Tahun 2016 Tentang Mediasi Perkara Perceraian di PA Jepara - Imron Choeri; Rani Fitriani (Faculty of Sharia and Law UNISNU Jepara, 2021)
This study aims for the first, analyzing Perma No. 1 year 2016 on the procedure of conducting mediation whether in accordance with the implementation of mediation in the Jepara Religious Court. Second, the effectiveness of mediation in divorce cases in the Jepara Religious Court. This research uses normative approach, using qualitative research type and using field research method, namely applied research or field research. To obtain the data is used documentation method. The results of this study stated that, first, most of the ones contained in Perma No. 1 of 2016 have been applied in the Jepara Religious Court, but there are some articles that are not in accordance with the latest Perma, for example the parties that must be in good faith at the time of mediation. Second, the effectiveness of mediation in the Jepara Religious Court, especially in divorce cases is very low, even many cases are entered but mediation can not be carried out. This is the need for socialization to the community the importance of carrying out mediation, whereas mediation is the most important process because to suppress the divorce rate in Jepara Regency.